Exporting Revolution : Cuba's Global Solidarity - Randall, Margaret, 1936- (Book collections on Project MUSE., 2017)
Margaret Randall explores the Cuban Revolution's impact on the outside world, tracing Cuba's international outreach in healthcare, disaster relief, education, literature, art, liberation struggles, and sports to show how this outreach is a fundamental characteristic of the Revolution and of Cuban society.